Polystyrene microplastics promote intestinal colonization of Aeromonas veronii through inducing intestinal microbiota dysbiosis - Wang, Yuqi (2024)
The premise that pathogen colonized microplastics (MPs) can promote the spread of pathogens has been widely recognized, however, their role in the colonization of pathogens in a host intestine has not been fully elucidated. Here, we investigated the effect of polystyrene MPs (PS-MPs) on the colonization levels of Aeromonas veronii, a typical aquatic pathogen, in the loach (Misgurnus anguillicaudatus) intestine. Multiple types of MPs were observed to promote the intestinal colonization of A. veronii, among which PS-MPs exhibited the most significant stimulating effect (67.18% increase in A. veronii colonization). PS-MPs inflicted serious damage to the intestinal tracts of loaches and induced intestinal microbiota dysbiosis. The abundance of certain intestinal bacteria with resistance against A. veronii colonization decreased, with Lactococcus sp. showing the strongest colonization resistance (73.64% decline in A. veronii colonization). Fecal microbiota transplantation was performed, which revealed that PS-MPs induced intestinal microbiota dysbiosis was responsible for the increased colonization of A. veronii in the intestine. It was determined that PS-MPs reshaped the intestinal microbiota community to attenuate the colonization resistance against A. veronii colonization, resulting in an elevated intestinal colonization levels of A. veronii.